Justice denied - Jance, Judith A., 1944- (Suspence ., 2008)
The murder of an ex-drug dealer ex-con-gunned down on his mother's doorstep-seems just another turf war fatality. Why then has Seattle homicide investigator J.P. Beaumont been instructed to keep this assignment hush-hush? Meanwhile, Beau's lover and fellow cop, Mel Soames, is involved in her own confidential investigation. Registered sex offenders from all over Washington State are dying at an alarming rate-and not all due to natural causes. A metropolis the size of Seattle holds its fair share of brutal crime, corruption, and dirty little secrets. But when the separate trails they're following begin to shockingly intertwine, Beau and Mel realize that they have stumbled onto something bigger and more frightening than they anticipated-a deadly conspiracy that's leading them to lofty places they should not enter . . . and may not be allowed to leave alive.